Crystallographic structural variations in nano-crystalline Sc2O3 under pressure. (1st April 2023) - Yadav, Deepa; Bura, Neha; Bhoriya, Ankit; Singh, Jasveer; Srihari, Velaga; Poswal, Himanshu K; Sharma, Nita Dilawar
Abstract: The present manuscript reports high-pressure investigations on nano-crystalline Scandium Oxide (Sc2 O3 ) through synchrotron angle dispersive x-ray diffraction technique (ADXRD) up to a pressure of ∼35.4 GPa using a diamond-anvil cell (DAC). The sample, having a cubic bixbyite structure at ambient conditions, underwent substantial changes in crystallographic parameters under the application of external pressure, while exhibiting phase stability i.e. does not undergo any structural phase transition up to 35.4 GPa. The lattice parameters and the unit cell volume decrease significantly with an increase in pressure, revealing the compressible nature of the crystal structure. The pressure-volume data is fitted using the third-order Birch-Murnaghan equation of state to calculate the bulk modulus and its first derivative, which yields zero pressure bulk modulus of 217(35) GPa, with B 0 ′ = 12(4) and the corresponding ambient volume per unit molecule comes out to be 59.18(18) Å 3 .